Functional status of pediatric patients with trauma and risk factors for mortality from a single center in China - Yang, Yu-Hang; Zhang, Tie-Ning; Yang, Ni; Xu, Wei; Wang, Li-Jie; Gao, Shan-Yan; Liu, Chun-Feng (Frontiers in Pediatrics, 2023)
Introduction This study aimed to identify the risk factors influencing the mortality rate in pediatric trauma survivors at a pediatric intensive care unit and to analyze their functional status using the Functional Status Scale (FSS). Methods A retrospective analysis was conducted at Shengjing Hospital of China Medical University. Children admitted to the pediatric intensive care unit between January 2015 and January 2020 who met the trauma diagnostic criteria were included. The FSS score and the Injury Severity Score (ISS) were collected upon admission and discharge, respectively. Clinical data were compared between the survival and non-survival groups to identify the risk factors for poor prognosis. The risk factors for mortality were identified using multivariate and univariate analyses. Results A total of 246 children (59.8%, male; median [IQR] age: 3 [1–7] years) were diagnosed with trauma (including head trauma, chest trauma, abdominal trauma, and extremity trauma). Of these patients, 207 were discharged, 11 dropped out mid-treatment, and 39 died (hospital mortality rate, 15.9%). Upon admission, the median FSS and trauma scores were 14 (IQR, 11–18) and 22 (IQR, 14–33) points, respectively. At discharge, the FSS score was 8 (IQR, 6–10) points. The patient clinical status improved with a ΔFSS score of −4 (IQR, −7, 0) points. At hospital discharge, 119 (48.3%), 47 (19.1%), 27 (11.0%), 12 (4.8%), and 2 (0.9%) survivors had good, mildly abnormal, moderately abnormal, severely abnormal, and very severely abnormal function, respectively. Dysfunction in patients was categorized as follows: motor, 46.4%; feeding, 26.1%; sensory, 23.2%; mental, 18.4%; and communication, 17.9%. In the univariate analysis, ISS >25 points, shock, respiratory failure, and coma were independently associated with the mortality rate. Multivariate analysis revealed that the ISS was an independent risk factor for mortality. Conclusions The mortality rate of patients with trauma was high. ISS was an independent risk factor for mortality. Mild dysfunction remained at discharge, and nearly half of the patients had dysfunction at discharge. Motor and feeding functions were the most severely impacted domains.